2022
DOI: 10.2147/ijn.s360271
|View full text |Cite
|
Sign up to set email alerts
|

Airspace Dimension Assessment with Nanoparticles (AiDA) in Comparison to Established Pulmonary Function Tests

Abstract: Background Airspace Dimensions Assessment with nanoparticles (AiDA) is a new method for non-invasive measurement of pulmonary distal airspaces. The aim of this study was to compare AiDA measurements with other pulmonary function variables to better understand the potential of AiDA in a clinical context. Methods AiDA measurements and pulmonary function tests were performed in 695 subjects as part of the Swedish CArdioPulmonary bioImage Study. The measurement protocol inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Similarly, to the previously mentioned study SCAPIS using AiDA on a larger Swedish population (n=695) aged 50-65 years, we found significant correlation between r AiDA and percent predicted FVC and FEV1 in dynamic spirometry as well as several IOS indices [27].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similarly, to the previously mentioned study SCAPIS using AiDA on a larger Swedish population (n=695) aged 50-65 years, we found significant correlation between r AiDA and percent predicted FVC and FEV1 in dynamic spirometry as well as several IOS indices [27].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to the previously mentioned study SCAPIS using AiDA on a larger Swedish population (n=695) aged 50–65 years, we found significant correlation between r AiDA and forced vital capacity (FVC) % predicted and FEV 1 in dynamic spirometry as well as several IOS indices [ 27 ]. In other studies, AiDA parameters were found to be correlated with results of 129 Xe DW-MRI [ 16 ] and CT of the lungs [ 15 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The observed decrease in R 0 can be explained by less deposition in the conducting airways at a shorter and shallower breathing cycle. However, R 0 measured at full in ation has earlier been shown to correlate with measures of lung heterogeneity [35,37]. The decreased R 0 at the smaller inhaled volume with particles could also be due to a larger in uence of entrainment and mixing with particle free air from the residual volume (the relative volume of air with particles is smaller at half in ation compared to the particle free air in the residual volume), which would strengthen the hypothesis that R 0 is a measure of lung heterogeneity.…”
Section: Aida At Half In Ationmentioning
confidence: 99%